2020
DOI: 10.26452/ijrps.v11ispl1.4550
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics and Physiotherapy: An overview of the role of the Physiotherapists in restoring functions and quality of life

Abstract: Pandemic is an epidemic that has becomes very widespread and affects the entire vicinity, a continent, and the world because of the vulnerable population. Management of pandemic consequence puts a great load on the healthcare sector. It demands great manpower from every sector for the smooth run of the daily essential services. Health care workers play a crucial role in delivering health care services during such pandemics. Physiotherapists are the allied health care professionals which provide primary, second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Another study revealed that elderly patients were unable to control the release of secretions using passive methods like vibration and postural drainage, which is also referred to as conventional physical therapy (CPT) [11][12][13]. On the other hand, a different study demonstrated that CPT could raise oxygenation and decrease secretions [14,15]. Postural drainage breathing exercises and mobility exercises were introduced to the chest therapy program after three days of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that elderly patients were unable to control the release of secretions using passive methods like vibration and postural drainage, which is also referred to as conventional physical therapy (CPT) [11][12][13]. On the other hand, a different study demonstrated that CPT could raise oxygenation and decrease secretions [14,15]. Postural drainage breathing exercises and mobility exercises were introduced to the chest therapy program after three days of admission.…”
Section: Discussionmentioning
confidence: 99%
“…It empowers the patients to enhance self-expression, accept and reconnect with their own bodies, cope with feelings of depression and fear, rebuild the shattered self-confidence, and strengthen personal resources. The group approach permits them to share their emotions and concerns, and also coping strategies with others [6,7]. DMT can be defined as the therapeutic use of movements that further enhances emotional, cognitive, and physical and the social integration of the individual [8].…”
Section: Introductionmentioning
confidence: 99%